Relationship between environmental manufacturing practices and their competitive outcomes (Journal of Mechanical Engineering, 2019)
In today’s competitive market providing products only in low cost and high quality is not enough.  Environmental concern in manufacturing is also an important issue now. To attract investors and customers organizations need to practice environmental manufacturing. This study is focused to present the relationships between some specific environmental manufacturing practices and their relative specific competitive outcomes in the important and vast industry of garment’s knitting sector in Bangladesh. Although there are several studies on the impact of environmental practices on the organizations outcomes but they are less construable due to many limitations. This study explores the environmental manufacturing practices under two categories pollution prevention and product stewardship and shows their relative competitive outcomes and establishes the relation between them. Based on the surveys and research it is found that some competitive outcomes are positively affected by some of the practices. These findings are believed to motivate the companies to turn towards the green manufacturing.